The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2018
DOI: 10.1007/s00586-018-5509-0
|View full text |Cite
|
Sign up to set email alerts
|

Radiological severity of hip osteoarthritis in patients with adult spinal deformity: the effect on spinopelvic and lower extremity compensatory mechanisms

Abstract: Patients with coexisting spinal malalignment and SOA compensate by pelvic shift and thoracic hypokyphosis rather than PT, likely as a result of limited hip extension secondary to SOA. As a result, SOA had worse global sagittal alignment than their LOA counterparts. These slides can be retrieved under Electronic Supplementary Material.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
35
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 40 publications
0
35
0
Order By: Relevance
“…A clinical study by Day et al showed a positive relationship between the sagittal spinal balance and severity of hip OA [10]. In particular, SVA and T1-Spi were higher in the severe OA group than in the limited OA group.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations
“…A clinical study by Day et al showed a positive relationship between the sagittal spinal balance and severity of hip OA [10]. In particular, SVA and T1-Spi were higher in the severe OA group than in the limited OA group.…”
Section: Discussionmentioning
confidence: 94%
“…We used population values and the sigma of the previous study and calculated the sample size with a probability of 0.05, effect size of 0.5, and power of 0.8. The analysis revealed that a minimum sample size of 44 was required for the study, so a total sample size of 47 cases was considered reasonable [10]. Third, this study did not consider lower extremity parameters and the morphology of the femur.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Owing to the coordinated nature of spinopelvic motions, a limit in motion on one spine segment tends to increase mobility in other spine segments and in pelvic tilt to maintain spinopelvic "balance" [1]. Spine diseases, including degenerative disc disease (DDD), degenerative spondylolisthesis, and lumbar fusion, have been associated with abnormal spinopelvic alignment and mobility [9,11,12].…”
Section: Conflict Of Interestsmentioning
confidence: 99%